Bahasa Inggris Calon Pustakawan Multitasking: Kiat-Kiat Menumbuhkan Minat Berbahasa Inggris Melalui Pendekatan Ramah Suasana - Rusmono, Doddy (Universitas Pendidikan Indonesia, 2015)
Abstract. Ideas expressed by LIS (Library and Information Science) students in the form of writing are incomprehensible to some extent. The work of LIS students of UPI, the librarians to-be, needs to be examined. These students are learners categorized as SNED (Students of Non English Department) gaining experience through learning English in the EFL (English as a Foreign Language) environments worth investigating. Lack of skill to bridge a gap between their native language (Indonesian) and target language (English) creates a room for inadequacy especially to native speakers. Paragraphs written by these students as ELLs (English Language Learners) are not easily understood due to the constraints dealing with linguistic and cultural barriers. A very small number of studentshave been willing to write their answers in English language when it comes toÂ options of answering in English or answering in Indonesian language in the mid-termexamination.This phenomenon gives a picture of competency in expresing ideas in English which is still far from being sufficient. Approach using a qualitative method of research with interview and observation as instruments to collect data from informants results in facts that they lack of confidence leading to an impact factor of low quality of writing. Hence, facilitators should take necessary steps to help with warm and friendly conduct toward betterments in working out English instead of Indonesian English. Librarians as professionals in practice should have a good command of English and exercise it in their daily routines. Their â€œat-homenessâ€ proves to be very low making it possible for a native speaker to misinterpret the original ideas of the ELLs. Culture as a factor influences and builds a sense, attitude, and response of the ELLs in interacting with a native speaker of the target language. It is found out that efforts with friendliness and pleasing approach bythe facilitators to make the ELLs feel comfortable plays an important part toward betterments.Key words: friendly atmosphere, paragraph writing, linguistic consraints, culture, SNED.Abstrak. Gagasan yang disampaikan dalam bentuk tertulis menggunakan Bahasa Inggris oleh Mahasiswa Program Studi Perpustakaan FIP-UPI, yang adalah calon Pustakawan, memerlukan penelitian. Para Mahasiswa ini adalah pembelajar yang berkategori SNED (Students of Non-English Department) yang belajar Bahasa Inggris dengan lingkungan EFL (English as a Foreign Language) yang menarik untuk diteliti. Kekurangmampuan menjembatani kesenjangan antara Bahasa Ibu mereka (Bahasa Indonesia) dengan Bahasa Penerima (Bahasa Inggris) menghambat keberterimaan oleh khususnya Penutur Asli (native speaker). Paragraf karya tulis SNED sebagai Pembelajar Bahasa Inggris (ELLs â€“English Language Learners) sering sulit dimengerti karena kendala linguistik dan kultur. Sedikit sekali Mahasiswa yang mau menulis didalam Bahasa Inggris pada UTS (UjianTengah Semester). Kenyataan ini menggambarkan betapa kemampuan Mahasiswamenyusun kalimat masih jauh dari memadai. Pendekatan menggunakan metode kualitatif dengan intrumen wawancara bersama informan menghasilkan simpulan bahwa lack of confidence onthe students' part merupakan impact factor. Teramati bahwa Bahasa Inggris yang digunakan masih merupakan Bahasa Inggris â€œIndonesiaâ€. Pada prakteknya, status Pustakawan Multitasking menuntut profesional Pustakawan untuk dapat berbahasa Inggris didalam rutinitas kesehariannya. Dalam hal ini, â€œat-homenessâ€ mereka masih rendah sehingga seorang native speaker yang mencoba memahami bahasa tulisan karya Pustakawan melakukan penafsiran yang keliru. Selain itu, pengetahuan ELLs mengenai kultur sasaran (Bahasa Inggris) memainkan peran sangat penting didalam berkomunikasi.Didalam menyampaikan gagasan mereka, para pembelajar ini mengalami kesulitan karena terkendala oleh kultur bahasa sasaran. Kultur ini mempengaruhi dan membentuk perasaan, sikap, dan respon ELLs didalam berinteraksi dengan penutur asli bahasa sasaran. Ditemukan bahwa upaya yang ramah dan menyenangkan dari pengajar selaku fasilitator untuk memperbaiki Bahasa Inggris para calon Pustakawan ini merupakan suatu keniscayaan.Kata kunci: ramah suasana, penulisan paragraf, kendala linguistik, kultur, SNED,.